Methylomics analysis identifies ZNF671 as an epigenetically repressed novel tumor suppressor and a potential non-invasive biomarker for the detection of urothelial carcinoma - Yeh, Chia-Ming (Impact Journals LLC, 2015)
The molecular mechanism underlying the lethal phenomenon of urothelial carcinoma (UC) tumor recurrence remains unresolved. Here, by methylation microarray, we identified promoter methylation of the zinc-finger protein gene, ZNF671 in bladder UC tumor tissue samples, a finding that was independently validated by bisulphite pyrosequencing in cell lines and tissue samples. Subsequent assays including treatment with epigenetic depressive agents and in vitro methylation showed ZNF671 methylation to result in its transcriptional repression. ZNF671 re-expression in UC cell lines, via ectopic expression, inhibited tumor growth and invasion, in possible conjunction with downregulation of cancer stem cell markers (c-KIT, NANOG, OCT4). Clinically, high ZNF671 methylation in UC tumor tissues (n=96; 63 bladder, 33 upper urinary tract) associated with tumor grade and poor locoregional disease-free survival. Quantitative MSP analysis in a training (n=97) and test (n=61) sets of voided urine samples from bladder UC patients revealed a sensitivity and specificity of 42%-48% and 89%-92.8%, respectively, for UC cancer detection. Moreover, combining DNA methylation of ZNF671 and 2 other genes (IRF8 and sFRP1) further increased the sensitivity to 96.2%, suggesting a possible three-gene UC biomarker. In summary, ZNF671, an epigenetically silenced novel tumor suppressor, represents a potential predictor for UC relapse and non-invasive biomarker that could assist in UC clinical decision-making.